Dynamic tightrope fixation for the correction of the 1,2 intermetatarsal angle in hallux valgus surgery - Samuel Ka-Kin Ling; Jojo Hoi-Ching Lai; Esther Man-Wai Chow; Lucci Lugee Liyeung; Arthur On-Fai Woo; Patrick Shu-Hang Yung (Journal of Orthopaedics, Trauma and Rehabilitation)
Introduction Hallux valgus is a common foot deformity that causes forefoot widening, difficulty fitting shoes, bunion pain, and transfer metatarsalgia. Studies have shown that correcting the 1,2 intermetatarsal angle (IMA) can significantly reduce forefoot width and improve symptoms. This study aims to review the radiological and functional outcomes of hallux valgus reconstruction with IMA closure using mini-tightrope suture buttons. Methods A case series of 52 consecutive patients who underwent minimally invasive surgical reconstruction of hallux valgus deformity utilising the dynamic tightrope fixation was included. All patients had >1 year follow-up with interim assessments at baseline, 3 months, 6 months, and 1 year. Primary outcomes included IMA in weight-bearing feet X-rays, and secondary outcomes included the hallux valgus angle (HVA) and clinical function via the Foot and Ankle Outcome Score. Results Based on radiological analysis, the 1,2 IMA and the HVA significantly improved. Clinical function also showed significant improvement in symptoms, pain, activities of daily living, and quality of life subsection. No major intra-operative complications occurred in this series; however, ∼5% of the patients required revision surgery due to a recurrence of the hallux valgus or overcorrection into hallux varus. Conclusion Dynamic tightrope fixation is a simple surgical technique that effectively corrects the 1,2 IMA during hallux valgus surgery.